Universal active network architecture and prototype application based on mobile agent technology - LIAO Xiao-fei; LI Jin-sheng; HONG Pei-lin; LIU Meng-juan; XIU Zhi-hua (Tongxin xuebao)
A universal active network architecture based on mobile agent technology was proposed, also a prototype application—active search engine founded on this architecture was put forward. Network simulations of this prototype application prove that this architecture has more merits and better performance on total time for task and network load.